2017
DOI: 10.3349/ymj.2017.58.3.489
|View full text |Cite
|
Sign up to set email alerts
|

Development of Inhibitors Targeting Hypoxia-Inducible Factor 1 and 2 for Cancer Therapy

Abstract: Hypoxia is frequently observed in solid tumors and also one of the major obstacles for effective cancer therapies. Cancer cells take advantage of their ability to adapt hypoxia to initiate a special transcriptional program that renders them more aggressive biological behaviors. Hypoxia-inducible factors (HIFs) are the key factors that control hypoxia-inducible pathways by regulating the expression of a vast array of genes involved in cancer progression and treatment resistance. HIFs, mainly HIF-1 and -2, have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
126
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(139 citation statements)
references
References 70 publications
1
126
0
3
Order By: Relevance
“…We not only construct the actual trilateral relations among M2 macrophages, autocrine VEGF and PD‐L1 expression for their role of immunomodulation, but also support a theory in biological aspect to explain how anti‐VEGF signalling turns to be a main character to enhance the effect of PD‐1 blockade in cancer therapy. Additionally, it highlights the value for the development of inhibitors targeting hypoxia‐inducible factor 1 and 2 in TAMs . Further investigation is needed to examine whether PD‐L1 + M2 macrophages stimulated by autocrine VEGF can be potent for immunotherapy of autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We not only construct the actual trilateral relations among M2 macrophages, autocrine VEGF and PD‐L1 expression for their role of immunomodulation, but also support a theory in biological aspect to explain how anti‐VEGF signalling turns to be a main character to enhance the effect of PD‐1 blockade in cancer therapy. Additionally, it highlights the value for the development of inhibitors targeting hypoxia‐inducible factor 1 and 2 in TAMs . Further investigation is needed to examine whether PD‐L1 + M2 macrophages stimulated by autocrine VEGF can be potent for immunotherapy of autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it highlights the value for the development of inhibitors targeting hypoxia-inducible factor 1 and 2 in TAMs. 35 Further investigation is needed to examine whether PD-L1 + M2 macrophages stimulated by autocrine VEGF can be potent for immunotherapy of autoimmune diseases.…”
Section: Corelation Of M2 Macrophages and Vegfmentioning
confidence: 99%
“…2ME2 is an endogenous metabolite of estradiol and is the most commonly employed HIF1α inhibitor. The mechanism for its inhibition on HIF1α in a human tumor cell line and in human umbilical vein endothelial cells is that 2ME2 inhibits HIF1α mRNA translation/de novo synthesis, and its association with microtubules, thereby blocking HIF1 nuclear accumulation and its transcriptional activity [39][40][41]. In the adult rodent brain, administration of 2ME2 before or soon after insult protected against global ischemia [42] or middle cerebral artery occlusion (MCAO)-induced brain damage [43,44], although 1 study reported that 2ME2 given 10 min after ischemia exacerbated apoptotic death in the CA1 region of the hippocampus following global ischemia [45].…”
Section: Discussionmentioning
confidence: 99%
“…The data we present appear to indicate that, in a hypoxic context, HT modulates different molecular mechanisms involved in tumor malignancy and resistance to therapy. The inhibition of the PI3K/Akt/mTOR pathway can overcome resistance to hormonal and anti-HER2 targeted therapies 83 , and HIF inhibitors are also promising molecules in cancer treatment 84 . Therefore, our data support that HT could have a chemomodulatory effect in breast cancer.…”
Section: Discussionmentioning
confidence: 99%